2011
DOI: 10.22229/fsp824385
|View full text |Cite
|
Sign up to set email alerts
|

Faculty and Student Perceptions of Incivility Behaviors in the Counselor Education Classroom

Abstract: A paucity of research exists on the topic of classroom incivility, defined as actions that disrupt the classroom learning environment, initiated by counseling graduate students and faculty. Through a quantitative descriptive survey design examining current perceptions of incivility in the graduate counseling classroom for both graduate students (N = 173) and faculty (N = 72), the authors found that (a) graduate students and faculty were consistent in their perceptions of the types, frequency, and severity of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Among them, the highest grades are given to behaviors like chatting, using the cell phone and being unprepared for the class (without basic supplies). This is in line with previous research (Paik & Broedel-Zaugg, 2006;Gannon-Leary, 2008;Bjorkland & Rehling, 2009Ausbrooks, Jones, & Tijerina, 2011Sterner, Jackson-Cherry & Doll, 2015). However, it should be mentioned that no matter how low the prevalence of some behavior might be, it still does not mean that it is a small problem for a teacher.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among them, the highest grades are given to behaviors like chatting, using the cell phone and being unprepared for the class (without basic supplies). This is in line with previous research (Paik & Broedel-Zaugg, 2006;Gannon-Leary, 2008;Bjorkland & Rehling, 2009Ausbrooks, Jones, & Tijerina, 2011Sterner, Jackson-Cherry & Doll, 2015). However, it should be mentioned that no matter how low the prevalence of some behavior might be, it still does not mean that it is a small problem for a teacher.…”
Section: Discussionsupporting
confidence: 90%
“…al. (2009) Sterner et al (2015) found that students view faculty actions taken to reduce incivility as less effective compared to faculty perceptions. Similary, Ausbrooks, Jones and Tijerina (2011) indicated that faculty tended to perceive disruptive behaviors less serious and frequent than students.…”
Section: Discussionmentioning
confidence: 99%